Contraparte sexual inconsciente en la elección de pareja maltratante en mujeres de 25 a 35 años que asisten al centro religiosas Adoratrices” de la ciudad de Quito - Campo Ortega, Karla Melissa (2015)
This work focuses on the study of the abuser partner choice as couple, by the users of the Centro de Capacitación de las Religiosas Adoratrices, and aims to investigate the process of couple choice, identifying the causes and development of it. This research takes as a base the concept of animus (the unconscious sexual counter-part of women), from the Jungian theory, and explains the process of introjection and projection of the male referent and how it strengthens and takes shape with every relationship of women with men, beginning with the father, uncles, brothers and then, the partner choice. A woman introjects throughout his life this male referent, which can be positive or negative, and later will be projected over her partner, a man similar to her animus qualities. Women with a negative animus will possibly choose as a couple (based on a projection mechanism) a man with the same characteristics of her negative animus: this can be appreciated in the users of the Centro de Capacitación de las Religiosas Adoratrices. The population of women observed along the research, have male referents related to abandonment and violence (by her father or another men throughout her life), and their relationships with men are often marked by abuse and contempt, along with men who nullify them, and end their life goals and objectives.